(untitled) (Economics and region, 2020)
In the article the peculiarities of formation of approaches to ensure sustainable development of modern cities in the national economy system in the conditions of globalization are considered. The changes in the formation, use and development of the total potential of cities under the influence of internal and external factors are studied. The author determined the trends in socio-economic development of cities and their impact on the model of sustainable development of the country. The state of sustainable development of cities and vulnerability of cities to the impact of external and internal factors characterizes the effectiveness of urban development management. The author proposed the approaches to developing a new concept of urban development management based on the principles of sustainable development taking into account its safety.